2010
DOI: 10.1186/1471-2350-11-20
|View full text |Cite
|
Sign up to set email alerts
|

A novel germline PALB2 deletion in Polish breast and ovarian cancer patients

Abstract: BackgroundPALB2 protein was recently identified as a partner of BRCA1 and BRCA2 which determines their proper function in DNA repair.MethodsInitially, the entire coding sequence of the PALB2 gene with exon/intron boundaries was evaluated by the PCR-SSCP and direct sequencing methods on 70 ovarian carcinomas. Sequence variants of interest were further studied on enlarged groups of ovarian carcinomas (total 339 non-consecutive ovarian carcinomas), blood samples from 334 consecutive sporadic and 648 consecutive f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
89
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(96 citation statements)
references
References 22 publications
4
89
2
1
Order By: Relevance
“…Similar to BRCA2, defects in the PALB2 gene are also associated with hereditary predisposition to male breast cancer (15,31) and pancreatic cancer (33)(34)(35) and according to some results they may also predispose to ovarian cancer (18,36). A comparison of cancer profiles in mutation-positive and -negative families in our study indicated only a weak association of PALB2 mutations with pancreatic and ovarian cancer.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Similar to BRCA2, defects in the PALB2 gene are also associated with hereditary predisposition to male breast cancer (15,31) and pancreatic cancer (33)(34)(35) and according to some results they may also predispose to ovarian cancer (18,36). A comparison of cancer profiles in mutation-positive and -negative families in our study indicated only a weak association of PALB2 mutations with pancreatic and ovarian cancer.…”
Section: Discussionsupporting
confidence: 59%
“…A founder PALB2 c.1592delT mutation, associated with a roughly 4-fold increased hereditary propensity for female breast cancer, was detected in Finland in 3 of 113 (2.7%) patients with familial breast cancer and in 18 of 1,918 (0.9%) unselected breast cancer cases. Until now, about 50 truncating mutations have been detected in breast cancer families worldwide and mutations have also been reported in cases of inherited pancreatic (33)(34)(35) and ovarian cancer (18,36). Therefore, PALB2 has been considered a strong candidate breast cancer-susceptibility gene; however, due to the limited number of studies, estimation of penetrance of breast cancer associated with PALB2 mutation has not been precisely determined (37).…”
Section: Introductionmentioning
confidence: 99%
“…Our cohort included 53 familial ovarian cancer patients, but no mutation was found in PALB2 in any of these cases. Recently, a Polish study tested a set of sporadic 70 ovarian carcinomas for PALB2 mutations [27]. Remarkably they found the same mutation (c.509_510delGA) as we did.…”
Section: Discussionmentioning
confidence: 53%
“…Coding sequences of the SMARCA4 gene with intron/exon boundaries were PCR-amplified and sequenced as previously described [8]. Some primer sequences were taken from a publication by Medina et al [9], while others were designed using the free Table I.…”
Section: Analysis Of the Smarca4 Gene Mutationsmentioning
confidence: 99%